Origin and development of agent nouns in -ino - Franz Rainer (Études romanes de Brno)
Agent nouns in -ino like postino (denominal) and spazzino (deverbal) are a specialty of Italo-Romance, concentrated in the dialects of Central and Northern Italy, and hence also present in the standard language, as well as in the neighboring Rhaeto-Romance territories influenced by Italian. Several explanations have been proposed concerning the origin of these agent nouns, none of which, however, is convincing. In the present paper, I defend the hypothesis that the denominal pattern arose in the context of the administration of Medieval cities by reanalyzing original diminutives. The deverbal pattern is considered an offshoot of the denominal pattern, due again to a reanalysis of ambiguous formations.